2020
DOI: 10.1101/2020.09.29.318170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PYL8 ABA receptors ofPhoenix dactyliferaplay a crucial role in response to abiotic stress and are stabilized by ABA (118)

Abstract: The identification of those prevailing ABA receptors and molecular mechanisms that trigger drought adaptation in crops well adapted to harsh conditions such as date palm (Phoenix dactylifera, Pd) sheds light on plant-environment interactions. We reveal that PdPYL8-like receptors are predominantly expressed under abiotic stress, being Pd27 the most expressed receptor in date palm. Therefore, subfamily I PdPYL8-like receptors have been selected for ABA signaling during abiotic stress response in this crop. Bioch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The PYL8 was reported to mediate ABA perception, and in turn ABA specifically stabilizes PYL8 and induces its accumulation in plant (Belda‐Palazon et al ., 2018; Garcia‐Maquilon et al ., 2021). Therefore, we examined whether exogenous ABA treatment would affect the interactions of IbPYL8 by Y2H and LCI assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PYL8 was reported to mediate ABA perception, and in turn ABA specifically stabilizes PYL8 and induces its accumulation in plant (Belda‐Palazon et al ., 2018; Garcia‐Maquilon et al ., 2021). Therefore, we examined whether exogenous ABA treatment would affect the interactions of IbPYL8 by Y2H and LCI assays.…”
Section: Resultsmentioning
confidence: 99%
“…AtPYL8 ‐overexpressing Arabidopsis plants were hypersensitive to ABA and exhibited high degrees of stomatal closure in response to ABA (Lim et al ., 2013). In date palm ( Phoenix dactylifera ), the PdPYL8‐like receptor Pd27 accumulated after ABA treatment, and Pd27 ‐overexpressing plants were more efficient than the WT in reducing transpiration under a negative soil water potential, leading to enhanced drought tolerance (Garcia‐Maquilon et al ., 2021). HvABI5 is involved in the ABA‐dependent drought response in barley (Collin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, PYL8-LIKE 27 was the most highly expressed at the yellow-to-brown transition (Fig. S2; Garcia-Maquilon et al, 2021). The identity of the signal that regulates the timing of the natural increase in fruit pericarp ABA levels and how it is related to the onset of fruit ripening remains to be determined.…”
Section: Is Aba a Multi-tasking Hormone?mentioning
confidence: 99%
“…The response to abiotic stress is usually accompanied by hormone regulation [29,30]. Analysis of the hormone-related cis-acting elements in GhCNGCs showed that the number of ABA-responsive cis-acting elements (60) was the highest (Table S5). ABA plays an important role in the regulatory response to salt and drought stress [30][31][32].…”
Section: Analysis Of Cis-acting Elements In Ghcngcsmentioning
confidence: 99%
“…Studies have reported that ABA plays a crucial role in the response to abiotic stress and is a central regulator of the abiotic stress response [60,61], leading to significant changes in gene expression and adaptive physiological responses [34]. Salt stress can induce the ABA signaling regulatory mechanism, which plays an important role in the regulation of plant salt tolerance [62,63].…”
Section: Functional Analysis Of the Ghcngc32 And Ghcngc35 Genes Invol...mentioning
confidence: 99%